Soil water balance dynamics on reclaimed mine land in the southwestern United States. (January 2017) - Byrne, Colin F.; Stormont, John C.; Stone, Mark C.
Abstract: Understanding the dynamics of soil water movement in arid and semi-arid environments is critical to successful reclamation of mined lands. Characteristics of applied topsoil impact soil water processes and long-term ecosystem health. The objective of this study was to better understand the soil water balance at a reclaimed mine in the southwestern United States through the investigation of soil hydraulic properties and subsequent one-dimensional water balance modeling. The study was conducted on a mine reclaimed using geomorphic principles. Complementary field and laboratory techniques were used to describe soil properties. Dry bulk density of topsoil at the mine sites increased with depth, while saturated hydraulic conductivity decreased with increasing bulk density. Two discrete one-dimensional models were created to investigate soil water dynamics and results indicate the importance of appropriately describing soil layering to create more accurate model predictions. In addition, results suggest that matric potentials during the study period were often too low for substantial plant growth. Models similar to those created in this study may be helpful in future assessment of seed germination on reclaimed lands as well as the implications that global climate change may have on reclamation strategies in the future. Highlights: Topsoil dry bulk density increased with soil depth at reclaimed watersheds. Topsoil saturated hydraulic conductivity decreased with increasing bulk density. Accurate description of soil layering proved critical in water balance modeling. Drought conditions limited soil water availability for vegetation establishment.